Pemberdayaan Perempuan Dalam Pengolahan Batang Pisang Untuk Mendukung Ekonomi Kerakyatan - Irma Irayanti; Aditya Rafly Ramadhan Wasirih; Muh. Alif Syahrial; Siti Nur Rahmawati; Nurul Magpira; Delia Triasma Ningsih (JPAI: Jurnal Perempuan dan Anak Indonesia, 2023)
Most of the Kastarib people are banana and coconut farmers because they see good potential in the business of planting bananas and coconuts in this area. Kastarib is an abundant producer of bananas. The abundance of bananas in Kastarib makes this sub-district the largest producer of dampo or sale of bananas on the mainland of Southeast Sulawesi. However, this is not in line with the increase in the welfare of the Kastarib community. This is caused by the people who lack the courage to innovate in the processing of bananas in their area. The large potential of banana resources in Kastarib Village, where the stems are wasted as trash, requires a creative and innovative effort to utilize banana stem waste into something that has market value and benefits for the community in Kastarib Village. The Participatory Action Research (PAR) approach is the choice in conducting community service in Kastarib Village which results in community understanding in innovating by making banana stem chips. The community, through the assistance of the Community Service team, succeeded in making a new innovative product, namely the processing of banana stems into chips of various flavors. Banana stems, which were only given to livestock as food, are now turning/innovating into delicious food and also rich in benefits. The banana stem chips became an exhibition product for Kastarib Village in the Bombana anniversary expo and became an attraction for the participants who attended the expo. It is hoped that this product will become the superior product of Kastarib Village ABSTRAK Masyarakat kastarib sebagian besar merupakan petani/pekebun pisang dan kelapa karena melihat potensi yang baik dalam usaha penanaman pisang dan kelapa di wilayah ini. Kastarib merupakan penghasil pisang yang melimpah.  Keberlimpahan pisang di Kastarib membuat Kelurahan ini sebagai penghasil dampo atau sale pisang terbesar di daratan Sulawesi Tenggara. Namun hal ini tidak sejalan dengan peningkatan kesejahteraan masyarakat Kastarib. Hal ini disebabkan oleh masyarakat yang kurang berani berinovasi dalam pengolahan pisang di daerahnya. Besarnya potensi sumber daya Pisang di Kelurahan Kastarib yang batangnya terbuang menjadi sampah membutuhkan suatu upaya kreatif dan inovatif dalam memanfaatkan limbah batang pisang menjadi sesuatu yang bernilai jual dan bermanfaat bagi masyarakat di Kelurahan Kastarib. Pendekatan Participatory Action Research (PAR) menjadi pilihan dalam melakukan pengabdian masyarakat di Kelurahan Kastarib yang menghasilkan pemahaman masyarakat dalam berinovasi dengan membuat keripik batang pisang. Masyarakat melalui pendampingan tim Pengabdian berhasil membuat produk inovasi baru yaitu pengolahan batang pisang menjadi keripik berbagai macam rasa, batang pisang yang tadinya hanya di berikan ke hewan ternak sebagai makanan, kini berubah/berinovasi menjadi makanan yg lezat dan juga kaya manfaat. Keripik batang pisang tersebut menjadi produk pameran Kelurahan Kastarib dalam kegiatan expo ulang tahun Bombana dan menjadi daya tarik bagi para peserta yang ikut hadir dalam kegiatan expo tersebut. Diharapkan produk ini menjadi produk unggulan Kelurahan Kastarib.